2019
DOI: 10.1007/s11191-019-00047-z
|View full text |Cite|
|
Sign up to set email alerts
|

Learning About Archaeology and Prehistoric Life

Abstract: This article is about an intervention introducing prehistoric life in primary education. Its objectives were to foster openness and interest for prehistory and archaeology, as well as content knowledge and conceptual learning with a focus on four main facets: basic knowledge about prehistoric life; conceptual learning/change regarding prehistory; learning about archaeologists and archaeology as a scientific discipline; and learning about interactions of archaeology and other disciplines (interdisciplinarity). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 73 publications
0
1
0
Order By: Relevance
“…In the workshops focused on experimental archaeology in the study by López-Castilla et al [2], it is observed how students learn about the main human activities of Prehistory, the tools and materials they used, and their connection with cultural, social, and economic evolution, being able to use the inductive and deductive method. In the same way, Besse et al [40] prove that in addition to achieving an increase in knowledge, there is also a better interpretation of the passage of time and its changes both in the short and long term, as is also replicated in the present work by observing how the students point out multi-causal historical and social changes around the Roman Baths of Valduno and the area where it is located at different historical moments.…”
Section: Discussionsupporting
confidence: 78%
See 2 more Smart Citations
“…In the workshops focused on experimental archaeology in the study by López-Castilla et al [2], it is observed how students learn about the main human activities of Prehistory, the tools and materials they used, and their connection with cultural, social, and economic evolution, being able to use the inductive and deductive method. In the same way, Besse et al [40] prove that in addition to achieving an increase in knowledge, there is also a better interpretation of the passage of time and its changes both in the short and long term, as is also replicated in the present work by observing how the students point out multi-causal historical and social changes around the Roman Baths of Valduno and the area where it is located at different historical moments.…”
Section: Discussionsupporting
confidence: 78%
“…Different studies indicate that students have some difficulty in pointing out the interdisciplinary nature of archaeology [40][41][42]. Despite this, the present results demonstrate that students recognize different ways of approaching an archaeological excavation, requiring different equipment and professionals from archaeology, historiography, and speleology in order to reach conclusive results [16].…”
Section: Discussionmentioning
confidence: 55%
See 1 more Smart Citation
“…This study revealed that the most valued teaching methodologies and activities are those that directly involve students and promote direct visits to the natural environment [35,41,62,63,91,92]. Specifically, the results showed a vivid interest in experiencing the gastronomic culture, which reveals the importance of sensory experiences in the appreciation and understanding of the rural environment and its traditions [49,52,[93][94][95].…”
Section: Discussionmentioning
confidence: 97%